ABSURDISME INDONESIA DALAM â€œSUMUR TANPA DASARâ€ KARYA ARIFIN C. NOER - Turahmat Turahmat; Jupriyanto Jupriyanto (PBSI, FKIP UNISSULA, Semarang, 2017)
The issue that arises from the limitations of absurdism on the drama's text is: is it possible that the drama STD (The Well Without Basic) by Arifin C.Noer does not in any way recognize the existence of God in his narrative? Another issue is how the form of absurdism in this drama text ?. This research utilizes a hermeneutic approach. Data were collected using reading technique and record technique. There are two sources of data in this study, namely primary data sources and secondary data sources. The primary data source in this research is the drama of No Drawing Well by Arifin C.Noer. The data contained in this research are words, phrases, clauses, or phrases in the drama dialogue of the Unfounded Wells by Arifin C.Noer which allegedly contains markers of drama absurdism. The data were analyzed using hermeneutic readings. Then presented in the form of a neatly arranged and systematic report. The forms of absurdism in this text lie in the following points. First, this drama uses the myth as a source of storytelling. Secondly, in this drama script also occur events outside the logic that utilize the human subconscious. The story of human life or figure in the drama script is oscillated in uncertainty. Third, the storyline in the drama script STD contains events that can still trace the plot. The existence of God still appears in this drama script. The traces of God's power also appear to be intertwined in several dialogues.